Norepinephrine and Phenylephrine for the Treatment of Hypotension During Spinal Anesthesia for Caesarean Section - Gagan Deep Singh; Atanu Mukherjee; Deepika Bagga (Academia Anesthesiologica International, 2021)
Background: To compare norepinephrine and phenylephrine for the treatment of hypotension during spinal anesthesia for caesarean section. Subjects and Methods: 104 American Society of Anesthesiologists I or II, primiparity, singleton, term pregnancy, elective caesarean section scheduled for spinal anesthesia were divided into two groups viz. Group P (phenylephrine) and group N (Norepinephrine). Following parameters such as systolic BP (SBP), Systolic blood pressure; HR: Heart rate; incidence of requirement for extra bolus, time to first extra bolus, and frequency of extra bolus, incidence of bradycardia was recorded. Results: The incidence of nausea, vomiting and dizziness was higher in group N as compared to group M. A significant difference was observed in two groups (P< 0.05). Time to first extra bolus was 5.2 minutes in group N and 5.7 minutes in group M, frequency of extra bolus was seen 1 in each group and incidence of bradycardia was seen among 2 in group N and 8 in group M. A non- significant difference was observed (P> 0.05). Conclusion: A greater SBP and a lower incidence of bradycardia with norepinephrine compared to phenylephrine for the management of maternal hypotension during elective cesarean section with spinal anesthesia.